RADT-28. RECURRENT MENINGIOMA WITH 1p/22q SOMATIC MUTATION OF GNAS: A CASE REPORT. (12th November 2021) - Hong, Weiping; Wen, Lei; Shan, Changguo; Ye, Minting; Yang, yanying; Wang, hui; Cai, Linbo
Abstract: OBJECTIVE: Refractory meningioma faces the problems of low total resection rate, high recurrence rate and high disability rate. Here we report a patient with recurrent refractory meningioma who was benefited from precision treatment plan based on molecular diagnosis. METHODS: Molecular diagnosis by next generation sequencing (NGS) test was used to test the hybridized captured DNA in the tumor tissue of the patient. RESULTS: The 53-year-old female diagnosed with meningioma was admitted to our hospital after tumor progression was observed for 3 weeks. She had received 4 operations for the tumor previously. The first three times of postoperative pathology indicated WHO Ⅰ grade meningioma. The fourth postoperative pathology showed excessive meningioma, with active growth of tumor cells in some areas and small focal necrosis, WHO Ⅰ- fair grade. Somatic mutation GNAS p.F309VFS *25 and deletion of the short arm of chromosome 1 / long arm of chromosome 22 were also found (1P / 22Q) by NGS test. The second recurrent foci showed partial amplification of 17q and 19, except for 1p/22q deletions, compared with the first. Meningiomas with 1p/22q deletion are type C meningiomas (more than half are grade WHO Ⅰ). Meningiomas have been shown to be highly vascularized neoplasms, with a 2-fold increase in VEGF expression in atypical meningiomas and a 10-fold increase in malignant meningiomas. According to the molecular diagnosis results, the precise treatment plan was determined: concurrent chemoradiotherapy, followed by anti-VEGF-targeted drugs combined with temozolomide for 2 months. The residual lesions were significantly reduced after treatment. CONCLUSION: This case is the first to report a meningioma with pituitary tumor driver gene GNAS mutation, which is more prone to recurrence due to the combination of 1P / 22Q chromosome mutation. Molecular diagnosis can guide precise treatment to benefit patients.